The influence of biological maturation on anthropometric determinants of talent identification among U-14 provincial girl tennis players - a pilot study : sport science - Van den Berg, Liandi; Coetzee, Ben; Pienaar, Anita E. (LAM Publications; AJOL; Sabinet, 2012)
The aim of this study was to determine whether biological maturation would significantly influence the anthropometric determinants of talent identification among U-14 provincial girl tennis players. Twenty-six of the top thirty-two provincial female players (mean age = 13.21 ± 0.72 years) from the Northern Gauteng and the North-West Province participated in the study. Twenty-eight anthropometric measurements were taken according to the protocols of The International Society for the Advancement of Kinanthropometry. Subjects completed a Biological Maturation Identification Questionnaire (BMIQ) on their stage of secondary sexual characteristics development and age of menarche as well as a few questions related to their demographic information, which facilitated the gathering of data on sport participation and South African ranking. The subjects were grouped into early (n = 4), average (n = 11) and late developers (n = 11) according to the BMIQ. The results of the Kruskal-Wallis ANOVA revealed no statistical significant differences between the anthropometric characteristics of the different biological maturation groups although certain trends with regard to differences were noted. Furthermore, results with regard to the ranking of the players showed that the late and average developer groups had the most seeded players. The findings suggest that the average and late developing female tennis players may surpass the early developers in their tennis performance.
Keywords: Kinanthropometry; Growth; Biological maturation; Girls; Tennis